Functional Patterns and Postural Balance Among Young Women with Chronic Non-Specific Low Back Pain and in Healthy Individuals - Aleksandra Adamik; Edyta Mikołajczyk (Rehabilitacja Medyczna)
Introduction: In the case of chronic low back pain, changes occur at the level of the central nervous system. This leads to limitations in functional and activity, as well as motor control impairments.Objectives: The aim of the study was to analyse the impact of chronic low back pain on the quality of performing functional patterns and postural balance in young women.Material and methods: The study involved 60 women at an average age of 21.571.07. In Group 1 (n=30), participants reported chronic low back pain, while Group 2 (n=30) was the control. To assess functional efficiency, the Functional Movement Screen was used. Postural stability was evaluated via the FreeMED Posture Base pedobarographic platform. Pain level was determined with the VAS scale, and pelvic anterior tilt was measured using the BROM II.Results: In the group of women with chronic low back pain, significantly lower levels of functional efficacy were observed. The distance covered by CoP, the area of an ellipse containing the trajectory of CoP, and the average velocity of CoP were greater compared to the group of women without pain. In Group 1, significantly greater asymmetry in foot pressure distribution was noted.Conclusions: Individuals reporting chronic low back pain demonstrate poorer quality of performing functional patterns and postural stability compared to healthy ones. Detecting movement disorders may contribute to a physiotherapist's planning of a therapeutic programme that considers specific movement deficits of patients. This can have direct impact on the reduction or delay of pain occurrence.